Understanding the Impact of Drug Legalization on Crime Rates: A Mixed-Methods Analysis - mukramin, Sam'un; Nurwandayani, Nurwandayani; Mulyadin , Dimas; Akhir , Syawal (Insan Akademika Publications, 2024)
This research investigates the intricate relationship between drug legalization and crime rates, aiming to provide insights into the effects of drug policy reforms on public safety and well-being. Adopting a mixed-methods approach, the study integrates quantitative analysis with qualitative insights to examine changes in crime rates following drug legalization measures. Diverse data sources, including official crime statistics, surveys, interviews, and qualitative data from stakeholders, are utilized to capture both macro-level trends and micro-level dynamics. Preliminary findings suggest that the impact of drug legalization on crime rates varies across different jurisdictions and drug types, with some areas experiencing reductions in certain types of crime while others show no significant changes or even increases in crime rates. Alternative explanations, such as socio-economic factors, law enforcement strategies, market dynamics, temporal trends, and data limitations, are considered to enrich the interpretation of observed patterns. Moving forward, continued monitoring and evaluation are essential to assess the stability and persistence of effects, inform evidence-based policymaking, and promote public safety, health, and well-being in communities worldwide.